The Influence of Audit Quality, Independent Board of Commissioners and Managerial Ownership on Profit Management (Case Study on Companies Included in LQ45 in the Indonesia Sharia Stock Index in 2019 -2023) - Efendi, Erizal Candra; Meirison (Politeknik Negeri Batam, 2025)
The primary goal of this research is to analyse the relationship between profit management and factors such managerial ownership, audit quality, and board of commissioners independence. Secondary sources are the backbone of this research. In particular, the LQ45 index members of the Indonesia sharia stock index for the years 2019